Mengenal Metaverse Dalam Pemasaran - Wijoyo, Agung; Cahya Firdaus, Indra; Mufti Prasetiyo, Sofyan (CV. Shofanah Media Berkah, 2024)
The phrase “metaverse” refers to the concept of an ever-expanding virtual world that offers new opportunities and changes various aspects of daily life, including marriage. The goal of this article is to investigate how metaverses can transform traditional marketing strategies by providing consumers with more immersive, interactive, and personalized experiences. In the metaverse, users can interact with other users through avatars and digital environments, enabling more mature and nuanced communication. This study uses case studies and literature analysis to identify best practices and barriers in developing a metaverse marketing strategy. Some forward-thinking individuals have utilized technologies such as virtual reality (VR) and augmented reality (AR) to create innovative marketing campaigns. For example, using avatars to represent oneself in cyberspace, launching products in cyberspace, and holding virtual events are some strategies that have proven successful. All research shows that the metaverse offers meaningful opportunities to increase customer loyalty and engagement. Immersive virtual and augmented reality experiences allow users to experience products and services in a highly realistic setting, enhancing their sense of touch and emotional connection with the brand. Additionally, virtual environments and avatar interactions allow users to collect more detailed and accurate consumer data, which can be used to personalize broader marketing strategies. This new Metaverse technology also presents various challenges. First, developing a robust digital infrastructure is critical to driving a seamless metaverse experience in the long term. Additionally, understanding consumer behavior in virtual environments is necessary to develop effective marketing strategies. Consumers may have different expectations and experiences in the metaverse compared to the real world, so they need to adapt and gain new experiences. One of the main strategies is to use augmented reality (AR) to create a more interactive learning experience. For example, AR can be used to allow customers to “try on” products such as clothing or furniture in a virtual environment before making a purchase. This not only increases profitability but also reduces product sales rates, which is often a problem in e-commerce. Another recognizable characteristic is the broadcast of virtual events. Through the use of virtual reality, businesses can use virtual reality to create products, content or other promotional events that can be seen by consumers around the world without the need for geographic restrictions. These kinds of events not only increase consumer exposure but also create unique and valuable experiences for them. The use of avatars as human representations is also becoming more common. In the metaverse, avatars can be used as brand messengers in consumer interactions, enabling more intimate and human interactions. Avatars can be customized to reveal a person's identity and interact with customers in a variety of ways, from providing product information to offering customer service. This study shows that the metaverse has the potential to become a major communication platform in the future. However, to realize this potential, collaboration between technological advances, market research, and policy development is needed to ensure that the metaverse develops in an intuitive, safe, and ethical manner. Businesses that successfully adapt and innovate in the metaverse will have a significant competitive advantage in attracting and retaining customers in the ever-evolving digital era.